Single shot 3 GeV electron transverse emittance with a pepper-pot - Thomas, C; Delerue, N; Bartolini, R (2013)
We present the first measurement of the transverse emittance of an electron bunch at 3 GeV using the pepper-pot technique. The measurements presented in this paper demonstrate the possibility to use such a method for single shot emittance measurement of high energy particles. This measurement presents also the experimental verification of a previous theoretical study, which was predicting in which condition such a measurement can be done. The method may present some technical limitations which are discussed in view of the application to future very small emittance multi-GeV particle accelerators. © 2013 Elsevier B.V.